Design of machine elements: SI edition - Spotts, M F; Shoup, Terry E; Hornberge, L E (Noida: Pearson, 2019)
About the book: The book has been completely SI metricated. This classic textbook on machine-design text contains 12 self-contained chapters covering the fundamental principles of this important branch of mechanical engineering. The material is drawn from a variety of sources and makes extensive use of structured computational examples to illustrate design applications.
Keywords: Mechanical Engineering; Design of shafts; Springs; Screws; Belts; Clutches; Brakes; Chains; Lubrication; Spur gears; Helical, bevel; worm gears